COVID-19 Crisis: Exploring Community of Inquiry in Online Learning for Sub-Degree Students - Lau, Yui-yip; Tang, Yuk Ming; Chau, Ka Yin; Vyas, Lina; Sandoval-Hernandez, Andres; Wong, Simon (Frontiers in Psychology, 2021)
The COVID-19 pandemic has brought a tremendous impact on the pedagogy and learning experience of students in sub-degree education sector of Hong Kong. Online learning has become the “sole” solution to deal with student learning challenges during this chaotic period. In this study, we explore online learning for sub-degree students by using a community of inquiry (CoI). As such, confirmatory factor analysis (CFA) was conducted on survey data gathered from 287 sub-degree students from the business and engineering disciplines. Results indicated that the network speed for online education determines the perceived cognitive presence, social presence, and teaching presence of students, whereas gender and academic disciplines of students are not moderating factors that create a significant difference in perceived cognitive presence, social presence, and teaching presence of students. Our study findings for creating and sustaining a purposeful online learning community are highlighted.